Job preferences of master public health candidates in Northeast China based on discrete choice experiments - Huaizhi Cheng; Ruotong Tian; Dongquan Chen; Jiesen Shang; Lingxiao Gao; Xiaoyu Dong; Bin Guo; Guoxiang Liu (BMC, 2024)
Abstract Background The shortage of health workers in rural and remote areas is a key issue for global health systems, including China. Public health undertakings in Northeast China face the risk of a talent gap. In September 2023, the National Development and Reform Commission (NDRC) held a symposium on promoting the comprehensive revitalization of Northeast China in the New Era, proposing to support the comprehensive revitalization of Northeast China with high-quality population development, strengthen the development and utilization of human resources, and increase policy support for the revitalization of talent. Methods The questionnaire was designed by discrete choice experiments, and 1208 Public Health Master's candidates from six universities in Northeast China were investigated online via the Powercx system network survey platform in April 2024. The mixed logit model was used to analyze the job preferences of Master Public Health candidates. Results All 7 attributes included in the study had statistically significant effects on the job preferences of public health master's degree candidates (P < 0.05). They tended to choose jobs with higher monthly income (12,000 CNY/month), located in cities with good working environments and with Bianzhi when seeking jobs. There is heterogeneity in job preference, and different preference characteristics are displayed in different subgroups. Conclusion This study revealed that public health master's degree candidates in Northeast China were more willing to choose jobs with higher monthly incomes, working places in cities and better working environments. The way to formulate a combination of policy packages is more attractive than improving a single aspect alone. Since the preferences of each subgroup are different, the preference characteristics of the target population should also be considered when formulating the policy package to meet the challenges of talent attraction and retention.